The association between childhood trauma and suicidal ideation in medical students: the role of alexithymia and resilience - Gao, Xiaomei; Mu, Siqi; Zhang, Daofen; Li, Ping; Wang, Wanrong; Hu, Xinyang; Wang, Peng (Frontiers in Psychiatry, 2025)
ObjectiveTo reveal the association between childhood trauma and suicidal ideation in medical students and explore the potential mediating roles of alexithymia and psychological resilience.MethodsBased on a cross-sectional survey conducted at a medical university in Anhui Province, 2,377 medical students were included. Assessments were performed using the Childhood Trauma Questionnaire, the Toronto Alexithymia Scale, the Resilience Scale, and the Suicidal Ideation Scale.ResultsOur results showed that childhood trauma significantly increased the risk of suicidal ideation in medical students (β=0.500, 95% CI: [0.470, 0.540]; The association was mediated by an alexithymia-resilience chain (mediating effect β=0.03, 95% CI: [0.029,0.040].ConclusionEmphasizing attention to medical students’ childhood trauma experiences, focusing on enhancing their emotion-processing abilities, and promoting psychological resilience represent effective strategies for preventing suicide risk in this population.